Small-scale industry in Latin America - United Nations Industrial Development Organization; Ecuador; United Nations (New York : United Nations, 1969)
This book is a comprehensive report on small scale industry in Latin America
At head of title: United Nations Industrial Development Organization, Vienna.
Sponsored by the Economic Commission for Latin America, and others in cooperation with the Government of Ecuador.
Includes bibliographical references.
oo 10/09/2018
Loans
Keywords: Small business